Instructional Supervision for Quality Education Delivery in Nigeria: Innovation Option for Effective Learners’ Achievement - Oyelade, Anthonia Ayobami; Egbebi, John Oluyemi (NIU Journal of Humanities; Vol 3 No 1 (2018): KIU Journal of Humanities, Vol. 3 No. 1, March 2018, 2018)
The paper examined instructional supervision approaches and management in basic and post basic schools to enhance best learners’ achievement as innovation tool for effective learners’ outcome. Specifically, the concept of instructional supervision, managers of instructional supervision, why instructional supervision in schools, challenges of instructional supervision, strategies for establishing quality assurance in education and the need to use internal supervisors versus external quality assurance personnel simultaneously in schools in Nigeria and see their impact on learners’ achievement in schools were extensively discussed. Conclusion and recommendations among others, were passed, such as the necessity to give more power and even in-service training programmes to the internal school managers as an on-going process in school instructional supervision in order to ensure enhanced academic performance of learners. Keywords: Instructional supervision, Quality assurance, Education, Service delivery, Innovation.